Development Patterns of Universal Design in Residential Courtyards in the Jugla Neighbourhood - Ile, Una; Bergmane, Lelde (Landscape Architecture and Art, 2023)
Quality and accessible outdoor living space in the immediate vicinity of one’s home is an important factor in ensuring people’s well-being, safety and community belonging. Access to building entrances is one of the key conditions for people to be able to reach the outdoors and enjoy equal mobility opportunities. Thus, one of the important challenges in achieving the principles and objectives of universal design on a small scale is related to building entrance areas. The building regulations at the time when most of Riga’s large-scale residential areas were built did not include requirements for environmental accessibility solutions. Most of the entrance areas of residential buildings and adjacent areas were constructed according to the construction practices of the time, using concrete steps to connect the carriageway level with the staircase doors. The study therefore includes conceptual solutions for environmental accessibility in building entrance areas - existing locations with specific environmental characteristics that would be applicable to as many building entrances as possible, regardless of the location of the buildings.